Understanding Women’s Responses to Sexual Pain After Female Genital Cutting: An Integrative Psychological Pain Response Model - Connor, Jennifer Jo; Brady, Sonya S.; Chaisson, Nicole; Mohamed, Fatima Sharif; Robinson, Beatrice “Bean” E. (Archives of sexual behavior, 2021)
The World Health Organization estimates that over 200 million women and girls have experienced female genital cutting (FGC). Many women and girls who have undergone FGC have migrated to areas of the world where providers are unfamiliar with the health needs associated with FGC. Both providers in Western healthcare systems and female immigrant and refugee patients report communication difficulties leading to distrust of providers by women who have experienced FGC. Sexual pain is one common problem requiring discussion with healthcare providers and possible intervention. Yet, existing clinical and research literature provides little guidance for assessment and intervention when sexual pain is a result of FGC. Several conceptual frameworks have been developed to conceptualize and guide treatments for other types of pain, such as back pain and headaches. In this article, we integrate four prominent models—the fear avoidance model, eustress endurance model, distress endurance model, and pain resilience model—to conceptualize sexual pain in women who have experienced FGC. The resulting integrative psychological pain response model will aid in providing culturally responsive clinical management of sexual pain to women who have experienced FGC. This integrative model also provides a theoretical foundation for future research in this population.